Efficiency of Bacterial Isolates in the Degradation of Malathion and Parathion - Kavi Karunya, S (International Journal of Pharmaceutical & Biological Archive, 2012)
Efficiency of Bacterial Isolates in the Degradation of Malathion and Parathion